2011
DOI: 10.3851/imp1906
|View full text |Cite
|
Sign up to set email alerts
|

Etravirine and Rilpivirine Resistance in HIV-1 Subtype Crf01_Ae-Infected Adults Failing Non-Nucleoside Reverse Transcriptase Inhibitor-Based Regimens

Abstract: Approximately 60% of patients had high-level ETR resistance. The role of ETR in second-line therapy is limited in late NNRTI failure settings. RVP RAMs were uncommon, but cross-resistance between ETR and RVP was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…A study focused on HIV-1 subtype CRF01_AE showed that the presence of mutations associated with resistance to rilpivirine are uncommon in patients infected by this subtype and failing a first-line NNRTI-containing regimen [183]. However, cross-resistance between rilpivirine and etravirine was high.…”
Section: Development Of Resistance To Antiretroviral Therapy Amongmentioning
confidence: 99%
See 1 more Smart Citation
“…A study focused on HIV-1 subtype CRF01_AE showed that the presence of mutations associated with resistance to rilpivirine are uncommon in patients infected by this subtype and failing a first-line NNRTI-containing regimen [183]. However, cross-resistance between rilpivirine and etravirine was high.…”
Section: Development Of Resistance To Antiretroviral Therapy Amongmentioning
confidence: 99%
“…However, cross-resistance between rilpivirine and etravirine was high. Moreover, approximately 60% of patients had a high level of etravirine resistance, thus suggesting that the role of etravirine in HIV-1 subtype CRF01_AE infected patients in second-line therapy is limited in late NNRTI failure settings [183]. …”
Section: Development Of Resistance To Antiretroviral Therapy Amongmentioning
confidence: 99%
“…In contrast, Y181C, which commonly occurs with nevirapine but not with efavirenz-containing regimens, confers partial cross-resistance to etravirine. [72] Given the complexity of determining residual activity to etravirine when NNRTI-associated mutations are present, a ‘genotypic susceptibility score’ (GSS) has been developed to predict etravirine susceptibility (figure 3). [58]…”
Section: Drug Resistance By Antiretroviral (Arv) Classesmentioning
confidence: 99%
“…This scenario increases the likelihood that a patient may harbour multiple minority variant NNRTI-resistant virus lineages, including some that may be associated with high-level etravirine resistance. [72,182]…”
Section: Salvage Therapymentioning
confidence: 99%
“…However, we failed to demonstrate this association in our study which may be due to 1) different immune responses in children compared to adults and a different HIV-1 clade. The majority of Thais are infected by HIV subtypes CRF01_AE [13]. There is limited data of APOBEC3G genotypes and association to the changes in HIV-RNA in populations infected with different HIV clades.…”
Section: Discussionmentioning
confidence: 99%